Il simil sync o semi-sinc nel panorama italiano: lo slittamento e offuscamento dei confini previsti dal CCNL (Altre Modernità, 2018)
Although Italy has always been a dubbing country, mainly due to cultural and historical reasons, the recent introduction of new TV formats, resulting from the hybridization between previously existing formats (such as docu-realities, a hybrid between documentaries and reality shows), has required the development of more suitable translation processes. Simil sync results from the hybridization between dubbing and voice-over, but it has not been clearly defined both from a theoretical point of view (as a separate branch within AVT, whose boundaries are blurred by the mentioned phenomenon of hybridization) and from a contractual point of view (the national collective agreement does not contain any reference to it and to its payment either). Consequently, the aim of the present work is to define simil sync as clearly as possible, also by providing a more suitable and less anglicized label for this translation practice (that is, semi-sinc).